DETERMINANTS OF MOTHER'S CHOICE OF PLACE DELIVERY IN COMMUNITY OF BAJO, MUNA DISTRICT: A QUALITATIVE STUDY - Imran, La Ode Ali; Asfian, Pitrah; tia, Rahma (Public Health of Indonesia, 2016)
Background: Muna is the area where Bajo community prefer to choose shaman for giving birth Objectives: This study aims to determine the reasons why mothers choose shamans or midwives to give birth in Renda Village, Towea Subdistrict, Muna District.Methods: This was a descriptive qualitative study to investigate determinants of mother's choice of place delivery in Renda Towea village of Muna, Indonesia. In-depth interview was performed to three mothers who gave birth with Shaman, and two mothers with Midwives. This study was conducted on July, 2016 in the village of Renda Towea, Muna district. Data were analyzed by content analysis model using Colaizzi's method of data analysis.Results: Results were grouped into: Reasons to choose midwives to give birth (Health concern, Family support, and Complete facilities), and Reasons to select shaman to give birth (Tradition, Financial concern, Short distance, Lack of information)Conclusions: Various reasons of mothers in choosing maternal care services. The findings of this study suggest that the government and health care providers should create the collaboration between midwives and shaman, increase financial support, and increase and evaluate health visitations to this community.